The Spatial Grasp Language - Sapaty, Peter S (European Journal of Applied Sciences, 2016)
A full description of a high-level language for solving arbitrary problems in heterogeneous, distributed and dynamic worlds, both physical and virtual, will be presented and discussed. The language is based on holistic and gestalt principles representing semantic level solutions in distributed environments in the form of self-evolving patterns. The latter are covering, grasping and matching the distributed spaces while creating active distributed infrastructures in them operating in a global-goal-driven manner but without traditional central resources. Taking into account the existing sufficient publications on the approach developed, the paper will be showing only elementary examples using the Spatial Grasp Language and key ideas of its networked implementation.